PROFITABILITAS SEBAGAI PEMODERASI HUBUNGAN PRAKTIK PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN - Hasti Putri Hulu; Anggun Dewi Santosa (Owner : Riset dan Jurnal Akuntansi, 2023)
The goal of the research is to examine the moderating effect of profitability on the effect of tax avoidance on a company's worth. Book Tax Difference is being used to quantify tax evasion as the independent variable in this analysis (BTD). The firm's TobinQ value will be used as the dependent variable in this study. The moderating factor is measured in terms of profitability, or more particularly return on equity (ROE). The LQ45 population consists of all companies listed on the Indonesia Stock Exchange between 2016 and 2020. Using a moderation regression model, we conducted test analysis on samples drawn from 165 companies over the period of 5 years using a purposeful sampling strategy. This study suggests that the market value of a firm might be significantly affected by tax evasion using the use of BTDs as proxies. As profits play no mediating role in the correlation between BTD proxy tax evasion and firm worth.